Question: Show that$$\int\limits_0^{\infty}\mathrm dx\,\frac {\arctan x\log(1+x^2)}{x(1+x^2)}=\frac {\pi}2\log^22.$$

I can't tell if I'm being an idiot, or if this is a lot more difficult than it looks. First, I tried integration by parts using the fact that $$\frac 1{x(1+x^2)}=\frac 1x-\frac x{1+x^2}.$$

But quickly I gave up as I wasn't sure what to do with the result. I then decided to make the substitution $t=\arctan x$ to get rid of the $1+x^2$ term in the denominator. Therefore$$\begin{align*}\mathfrak{I} & =\int\limits_0^{\pi/2}\mathrm dt\,t\cot t\log\sec^2t=-2\int\limits_0^{\pi/2}\mathrm dt\, t\cot t \log\cos t.\end{align*}$$

However, I'm not exactly sure what to do after this. Should I use integration by parts? Differentiation under the integral sign? I'm having trouble getting started with this integral. Any ideas?

  • 4
    $\begingroup$ If I may ask, but why the close vote? I doubt my question is off topic, and furthermore, I included my two main attempts. Other attempts would be expanding $\log$ in its taylor expansion series and a similar thing with the $\arctan$ function. $\endgroup$
    – Frank
    Jul 14 '18 at 0:49
  • $\begingroup$ After an hour I’m not optimistic for a closed form. I think you need something fancy here. $\endgroup$
    – Randall
    Jul 14 '18 at 1:28
  • $\begingroup$ Side note: The integral occurs in this question as well. $\endgroup$ Jul 14 '18 at 21:07

We can use differentiation under the integral sign and a trick to evaluate this. First define $$ I(a,b) = \int_0^{\infty} \frac{\arctan{ax}}{x} \frac{\log{(1+b^2 x^2)}}{1+x^2} \, dx , $$ so $I(a,0)=I(0,b)=0$ and $I(1,1)$ is what we want. Differentiating one with respect to $a$ and once wrt $b$ gives $$ \partial_a\partial_b I = \int_0^{\infty} \frac{2bx^2 \, dx}{(1+x^2)(1+a^2x^2)(1+b^2x^2)}, $$ which can be done by using partial fractions and the arctangent integral a few times. When the dust settles, $$ \partial_a\partial_b I = \frac{b\pi}{(1+a)(1+b)(a+b)}, $$ and thus $$ I(1,1) = \int_0^1 \int_0^1 \frac{b\pi}{(1+a)(1+b)(a+b)} \, da \, db $$ But we can swap $a$ and $b$ and will get the same result for this integral by the symmetry of the region of integration, so we also have $$ I(1,1) = \int_0^1 \int_0^1 \frac{a\pi}{(1+a)(1+b)(a+b)} \, da \, db. $$ Adding gives $$ I(1,1) = \frac{\pi}{2}\int_0^1 \int_0^1 \frac{1}{(1+a)(1+b)} \, da \, db, $$ but this splits into a product of two copies of $\int_0^1 dy/(1+y) = \log{2}$, so $$ I(1,1) = \frac{\pi}{2}(\log{2})^2 $$ as desired.

  • 3
    $\begingroup$ Nice answer! +1 $\endgroup$
    – Tom Himler
    Jul 14 '18 at 2:02
  • $\begingroup$ Oh lord, I’ve completely forgotten about Feynman’s Trick! Why didn’t I think of that! Although I’m not very familiar with differentiation with two variables. How did you know to use two variables instead of say, just setting the $a$ there? To me, having $\arctan ax$ and $\log(1+b^2x^2)$ is an overcomplication. $\endgroup$
    – Frank
    Jul 14 '18 at 3:21
  • $\begingroup$ I have forgotten: when is differentiation under the integral allowed? $\endgroup$
    – Randall
    Jul 14 '18 at 13:22
  • $\begingroup$ @Frank I did try only using one derivative, but it resulted in a rather nasty log that would have required a polylogarithm to integrate. Indeed, this trick only works because $a=b$ in the limit we care about, so we can apply a symmetry to make the integral much nicer; the general case will involve polylogarithms. $\endgroup$
    – Chappers
    Jul 14 '18 at 20:10
  • $\begingroup$ @Randall $\partial_a f(x,a)$ integrable and $\frac{1}{h}\int | f(x,a+h)-f(x,a) - h \partial_a f(x) | dx \to 0$ should be sufficient in general. Dominated Convergence will cover most explicit cases, including this one since there's always a $1/(1+x^2)$ involved. But everything's positive here as well, so one can also view it as an application of Tonelli to permute the order of integration. $\endgroup$
    – Chappers
    Jul 14 '18 at 20:14

Define $$ f(a,b) = \int \limits_0^\infty \frac{\arctan(a x) \ln (1+ b^2 x^2)}{x (1+x^2)} \, \mathrm{d} x $$ for $0 \leq a , b \leq 1$ . Then $f(1,1) = \mathfrak{I}$ and $f(0,b) = f(a,0) = 0 $ . For $0< a,b<1$ we can differentiate under the integral sign to find $$ \partial_a \partial_b f(a,b) = 2 b \int \limits_0^\infty \frac{x^2}{(1+a^2 x^2)(1+b^2 x^2)(1+x^2)} \, \mathrm{d} t = \frac{\pi b}{(1+a)(1+b)(a+b)} \, . $$ The integral can be evaluated using the residue theorem, for example. Now integrate again and exploit the symmetry of the derivative to obtain \begin{align} \mathfrak{I} &= f(1,1) = \pi \int \limits_0^1 \int \limits_0^1 \frac{b}{(1+a)(1+b)(a+b)} \, \mathrm{d}a \, \mathrm{d}b = \pi \int \limits_0^1 \int \limits_0^1 \frac{a}{(1+a)(1+b)(a+b)} \, \mathrm{d}a \, \mathrm{d}b \\ &= \frac{\pi}{2} \int \limits_0^1 \int \limits_0^1 \frac{a+b}{(1+a)(1+b)(a+b)} \, \mathrm{d}a \, \mathrm{d}b = \frac{\pi}{2} \int \limits_0^1 \int \limits_0^1 \frac{1}{(1+a)(1+b)} \, \mathrm{d}a \, \mathrm{d}b \\ &= \frac{\pi}{2} \ln^2 (2) \, . \end{align}



$$ \Im(\log^2(1+ix))=\Im\left(\left(\frac{1}{2}\log(1+x^2)+i\arctan(x)\right)^2\right)=\frac{1}{2}\log(1+x^2)\arctan(x) $$

The integral in question is therefore (use parity) $$ I=\Im\int_{\mathbb{R}}\underbrace{\frac{\log^2(1+ix)}{x(1+x^2)}}_{f(x)} $$

Integrate around a big semicircle in the lower halfplane (to avoid the branchcut) yields

$$ I=\Im \left(2\pi i\text{Res}(f(z),z=-i)\right)=\frac{\pi}{2}\log^2(2)$$

where the residue is easy to calculate since the pole is simple.

The vansihing of the contrbutions at infinity follows from the fact that $R|f(Re^{i\phi})|\sim \log^2(R)/R^2$ in sector of $\mathbb{C}$ we are interested in.

  • $\begingroup$ You also need that the integrand is even (to change the integral into one over $\mathbb{R}$), and that the singularity at zero is removable (so it doesn't contribute to the integral at all). $\endgroup$
    – Chappers
    Jul 14 '18 at 20:17

\begin{align}J&=\int_0^\infty \frac{\ln(1+x^2)\arctan x}{x(1+x^2)}dx\\ &=\int_0^1 \frac{\ln(1+x^2)\arctan x}{x(1+x^2)}dx+\int_1^\infty \frac{\ln(1+y^2)\arctan y}{y(1+y^2)}dy\\ &\overset{x=\frac{1}{y}}=\int_0^1 \frac{\ln(1+x^2)\arctan x}{x(1+x^2)}dx+\int_0^1 \frac{x\ln\left(\frac{1+x^2}{x^2}\right)\arctan\left( \frac{1}{x}\right)}{1+x^2}dx\\ &=\int_0^1 \frac{\ln(1+x^2)\arctan x}{x}dx-2\int_0^1 \frac{x\ln(1+x^2)\arctan x}{1+x^2}dx+2\int_0^1 \frac{x\ln x\arctan x}{1+x^2}dx+\\ &\frac{\pi}{2}\int_0^1 \frac{x\ln(1+x^2)}{1+x^2}dx-\pi\int_0^1 \frac{x\ln x}{1+x^2}dx\\ &\overset{\text{IBP}}=\int_0^1 \frac{\ln(1+x^2)\arctan x}{x}dx-2\int_0^1 \frac{x\ln(1+x^2)\arctan x}{1+x^2}dx+\\&\Big[\ln(1+x^2)\ln x\arctan x\Big]_0^1-\int_0^1 \frac{\ln(1+x^2)\arctan x}{x}dx-\int_0^1 \frac{\ln(1+x^2)\ln x}{1+x^2}dx+\\&\frac{\pi}{2}\int_0^1 \frac{x\ln(1+x^2)}{1+x^2}dx-\pi\int_0^1 \frac{x\ln x}{1+x^2}dx\\ &=-2\int_0^1 \frac{x\ln(1+x^2)\arctan x}{1+x^2}dx-\int_0^1 \frac{\ln(1+x^2)\ln x}{1+x^2}dx+\frac{\pi}{2}\int_0^1 \frac{x\ln(1+x^2)}{1+x^2}dx-\\&\pi\int_0^1 \frac{x\ln x}{1+x^2}dx\\ K&=\int_0^1 \frac{2x\ln(1+x^2)\arctan x}{1+x^2}dx\\ &\overset{\text{IBP}}=\Big[\ln(1+x^2)^2\arctan x\Big]_0^1-K-\int_0^1 \frac{\ln^2(1+x^2)}{1+x^2}dx\\ K&=\frac{\pi\ln^2 2}{8}-\frac{1}{2}\int_0^1 \frac{\ln^2(1+x^2)}{1+x^2}dx\\ J&=-\frac{\pi\ln^2 2}{8}+\frac{1}{2}\int_0^1 \frac{\ln^2(1+x^2)}{1+x^2}dx-\int_0^1 \frac{\ln(1+x^2)\ln x}{1+x^2}dx+\frac{\pi}{2}\int_0^1 \frac{y\ln(1+y^2)}{1+y^2}dy-\\&\pi\int_0^1 \frac{y\ln y}{1+y^2}dy\\ &\overset{x=y^2}=-\frac{\pi\ln^2 2}{8}+\frac{1}{2}\int_0^1 \frac{\ln^2(1+x^2)}{1+x^2}dx-\int_0^1 \frac{\ln(1+x^2)\ln x}{1+x^2}dx+\frac{\pi}{4}\int_0^1 \frac{\ln(1+x)}{1+x}dx-\\&\frac{\pi}{4}\int_0^1 \frac{\ln x}{1+x}dx\\ &=\frac{1}{2}\int_0^1 \frac{\ln^2(1+y^2)}{1+y^2}dy-\int_0^1 \frac{\ln(1+y^2)\ln y}{1+y^2}dy-\frac{\pi}{4}\int_0^1 \frac{\ln x}{1+x}dx\\ &\overset{y=\tan t}=2\int_0^{\frac{\pi}{4}}\ln^2\left(\cos t\right)dt-2\int_0^{\frac{\pi}{4}}\ln^2\left(\cos t\right)dt+2\int_0^{\frac{\pi}{4}}\ln\left(\cos t\right)\ln\left(\sin t\right)dt-\\&\frac{\pi}{4}\int_0^1 \frac{\ln x}{1+x}dx\\ &=2\int_0^{\frac{\pi}{4}}\ln\left(\cos t\right)\ln\left(\sin t\right)dt-\frac{\pi}{4}\int_0^1 \frac{\ln x}{1+x}dx\\ &=\frac{1}{2}\left(\int_0^{\frac{\pi}{4}}\ln^2(\sin t\cos t)dt-\int_0^{\frac{\pi}{4}}\ln^2\left(\tan u\right)du\right)-\frac{\pi}{4}\int_0^1 \frac{\ln x}{1+x}dx\\ &\overset{u=2t}=\frac{1}{4}\int_0^{\frac{\pi}{2}}\ln^2\left(\frac{\sin u}{2}\right)du-\frac{1}{2}\int_0^{\frac{\pi}{4}}\ln^2\left(\tan u\right)du-\frac{\pi}{4}\int_0^1 \frac{\ln x}{1+x}dx\\ &=\frac{1}{4}\int_0^{\frac{\pi}{2}}\ln^2\left(\sin u\right)du-\frac{\ln 2}{2}\int_0^{\frac{\pi}{2}}\ln\left(\sin u\right)du+\frac{\pi\ln^2 2}{8}-\frac{1}{2}\int_0^{\frac{\pi}{4}}\ln^2\left(\tan u\right)du-\\&\frac{\pi}{4}\int_0^1 \frac{\ln x}{1+x}dx\\ L&=\int_0^{\frac{\pi}{2}}\ln^2\left(\sin u\right)du\\ &=\frac{1}{4}\left(2\int_0^{\frac{\pi}{2}}\ln^2\left(\sin u\right)du+2\int_0^{\frac{\pi}{2}}\ln^2\left(\cos u\right)du\right)\\ &=\frac{1}{4}\left(\int_0^{\frac{\pi}{2}}\ln^2\left(\cos u\sin u\right)du+\int_0^{\frac{\pi}{2}}\ln^2\left(\tan u\right)du\right)\\ &\overset{t=2u}=\frac{1}{4}\left(\frac{1}{2}\int_0^{\pi}\ln^2\left(\frac{\sin t}{2}\right)dt+\int_0^{\frac{\pi}{2}}\ln^2\left(\tan u\right)du\right)\\ &=\frac{1}{8}\int_0^{\pi}\ln^2\left(\sin t\right)dt-\frac{\ln 2}{4}\int_0^{\pi}\ln\left(\sin t\right)dt+\frac{\pi\ln^2 2}{8}+\frac{1}{4}\int_0^{\frac{\pi}{2}}\ln^2\left(\tan u\right)du\\ &=\frac{1}{8}\left(L+\int_{\frac{\pi}{2}}^\pi\ln^2\left(\sin v\right)dv\right)-\frac{\ln 2}{4}\int_0^{\pi}\ln\left(\sin t\right)dt+\frac{\pi\ln^2 2}{8}+\frac{1}{4}\int_0^{\frac{\pi}{2}}\ln^2\left(\tan u\right)du\\ &\overset{t=\pi-v}=\frac{1}{4}L-\frac{\ln 2}{4}\int_0^{\pi}\ln\left(\sin t\right)dt+\frac{\pi\ln^2 2}{8}+\frac{1}{4}\int_0^{\frac{\pi}{2}}\ln^2\left(\tan u\right)du\\ L&=-\frac{\ln 2}{3}\int_0^{\pi}\ln\left(\sin t\right)dt+\frac{\pi\ln^2 2}{6}+\frac{1}{3}\int_0^{\frac{\pi}{2}}\ln^2\left(\tan u\right)du\\ &=-\frac{\ln 2}{3}\int_0^{\frac{\pi}{2}}\ln\left(\sin t\right)dt-\frac{\ln 2}{3}\int_{\frac{\pi}{2}}^{\pi}\ln\left(\sin v\right)dv+\frac{\pi\ln^2 2}{6}+\frac{1}{3}\int_0^{\frac{\pi}{2}}\ln^2\left(\tan u\right)du\\ &\overset{t=\pi-v}=-\frac{2\ln 2}{3}\int_0^{\frac{\pi}{2}}\ln\left(\sin t\right)dt+\frac{\pi\ln^2 2}{6}+\frac{1}{3}\int_0^{\frac{\pi}{2}}\ln^2\left(\tan u\right)du\\ \end{align}


\begin{align}J&=\frac{1}{6}\pi\ln^2 2-\frac{\pi}{4}\int_0^1 \frac{\ln x}{1+x}dx-\frac{2\ln 2}{3}\int_0^{\frac{\pi}{2}}\ln\left(\sin t\right)dt+\frac{1}{12}\int_0^{\frac{\pi}{2}}\ln^2\left(\tan t\right)dt-\\&\frac{1}{2}\int_0^{\frac{\pi}{4}}\ln^2\left(\tan t\right)dt\\ &=\frac{1}{6}\pi\ln^2 2-\frac{\pi}{4}\int_0^1 \frac{\ln x}{1+x}dx-\frac{2\ln 2}{3}\int_0^{\frac{\pi}{2}}\ln\left(\sin t\right)dt+\\&\frac{1}{12}\left(\int_0^{\frac{\pi}{4}}\ln^2\left(\tan t\right)dt+\int_{\frac{\pi}{4}}^{\frac{\pi}{2}}\ln\left(\tan u\right)du\right)-\frac{1}{2}\int_0^{\frac{\pi}{4}}\ln^2\left(\tan t\right)dt\\ &\overset{t=\frac{\pi}{2}-v}=\frac{1}{6}\pi\ln^2 2-\frac{\pi}{4}\int_0^1 \frac{\ln x}{1+x}dx-\frac{2\ln 2}{3}\int_0^{\frac{\pi}{2}}\ln\left(\sin t\right)dt-\frac{1}{3}\int_0^{\frac{\pi}{4}}\ln^2\left(\tan t\right)dt\\ &=\frac{1}{6}\pi\ln^2 2-\frac{\pi}{4}\times -\frac{\pi^2}{12}-\frac{2\ln 2}{3}\times -\frac{\pi\ln 2}{2}-\frac{1}{3}\times \frac{\pi^3}{16}\\ &=\boxed{\frac{\pi\ln^2 2}{2}} \end{align}

I assume that:

\begin{align}\int_0^{\frac{\pi}{4}}\ln^2\left(\tan t\right)dt&=\frac{\pi^3}{16}\\ \int_0^1 \frac{\ln x}{1-x}dx&=-\zeta(2)=-\frac{\pi^2}{6}\\ \int_0^{\frac{\pi}{2}}\ln\left(\sin t\right)dt&=-\frac{\pi\ln 2}{2}\\ \int_0^1 \frac{\ln x}{1+x}dx&=\int_0^1 \frac{\ln x}{1-x}dx-\int_0^1 \frac{2y\ln y}{1-y^2}dy\\ &\overset{y=x^2}=\frac{1}{2}\int_0^1 \frac{\ln x}{1-x}dx=-\frac{\pi^2}{12} \end{align}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.